Self-checking method for fault tolerance solution in wireless sensor network - Muayad Sadik Croock; Saja Dhyaa Khuder; Zahraa Abbas Hassan (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Recently, the wireless sensor network (WSN) has been considered in different application, particularly in emergency systems. Therefore, it is important to keep these networks in high reliability using software engineering techniques in the field of fault tolerance. This paper proposed a fault node detection method in WSN using the self-checking technique according to the rules of software engineering. Then, the detected faulted node is covered employing the reading of nearest neighbor nodes (sensors). In addition, the proposed method sends a message for maintenance to solve the fault. The proposed method can reduce the time between the detection and recovery of a fault to prevent the confusion of adopting wrong readings, in which the detection is making with mistake. Moreover, it guarantees the reliability of the WSN, in terms of operation and data transmission. The proposed method has been tested over different scenarios and the obtained results show the superior efficiency in terms of recovery, reliability, and continuous data transmission.